Public Private Partnership Financiers’ Perceptions of Risks - Istemi Demirag, Queens University Belfast Iqbal Khadaroo University of Essex Pamela Stapleton University of Manchest (The Institute of Chartered Accountants of Scotl, 2010)
Public private partnerships (PPP) are an established model for governments internationally to provide infrastructure-based services. They involve a clearly defined project financed by the private sector, which shares the associated risks and rewards with the public sector. Typically the public sector procurer will sign a contract with a special purpose vehicle (SPV) which subcontracts the finance, design, construction, maintenance and soft services to companies that are often related to its shareholders. This study focuses mainly on the financiers in this network of organisations, and examines their perceptions of the risks involved in the investment of equity and senior debt in PPP. Private sector involvement in the provision of public services is not new but the PPP model enables and encourages more private sector involvement in the provision of public services. The scale of projects involving private finance is significant and PPP is used widely across the public sector. While a number of advanced Organisation for Economic Co-operation and Development (OECD) countries now have wellestablished PPP programmes, the best developed is the UK’s (IMF, 2004). Since the inception of the policy in the 1990s, the total capital value of signed deals in the UK reached some £63 billion by the end of 2008. PPP spending currently represents some 10% of total government investment. Although the new coalition government is expected to significantly curtail investment in infrastructure projects, it is likely that it will favour private sector involvement in any such future projects. Despite the rapid growth in the market, very little research has investigated the role of the financiers in PPP, although a growing body of research examines the projects from the perspectives of the public sector procurers and the private sector contractors. The contribution of this study is its focus on the role of financiers.